Art exchanges in south-east Europe vol. 1. : Thessaloniki, Greece : lectures, discussion groups, agor'art café, exhibitions. - Angel, Judit; Badovinac, Zdenka; Bainier, Jean-Yves; Dimova, Dessislava; Djuric, Uros; Dracodaidis, Philip; Dumont, Fabienne; Grzinic, Marina; Hegyi, Lóránd; Jancar, Ivan; Konstantinidis, Dimitri; Konteletzidou, Dorothea; et al. (Strasbourg : Apollonia European Art Exchanges, 2000)
The Greek Ministry of Culture has instructed Apollonia and the Contemporary Art Center Thessaloniki to organise a meeting in Thessaloniki from 5th to 7th October 2000 devoted to art exchanges in south-eastern Europe. At the same time, two exhibitions will be on display until 8th November in Thessaloniki and then at the Rethymnon Contemporary Art Centre (Crete). The purpose of the operation is to bring together the various people involved in culture in the Balkan countries with a view to drawing up an inventory of the current situation, to propose new directions for art exchanges, and to create genuine prospects and projects for partnerships and collaboration among the various countries in this region, and also with other European countries. This multilateral meeting will bring together more than a hundred people - artists, art critics, representatives of cultural institutions and bodies, of private cultural foundations, museums and other artistic structures , representatives of the States and of the European institutions, and independent art operators.
Bratkov, Sergey ; Chekorsky, Vadim ; Chichkan, Illya ; Dulfan, Dmitry ; Kozhuhar, Vladimir ; Kulchitsky, Miroslav ; Kulik, Oleg ; Mamsikov, Maksim ; Mikhailov, Boris ; Moskvichev, Andriy ; Solonsky, Sergiy ; Tsagolov, Vasyly ; Dvali, Manana ; Khakhanashvili, Shalva ; Ramischwili, Koka ; Timchenko, Oleg ; Tsetskhiadze, Nikoloz ; Zautaschwili, Iliko
presentation of the participants = présentation des participants (biog.) p. 105-137
Engels & Frans & Grieks
Art exchanges in south-east Europe, October 4th - November 8th 2000, Exhibitions : "The other side of the History", "Contemporary photographers of Ukraine", Cultural Foundation of the Bank of Greece, Thessaloniki
kunstcatalogus
Keywords: Balkan; Bulgarije; Griekenland; Joegoslavië; Kroatië; Oekraïne; Slovakije; Turkije; Zuid-Oost Europa